PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS MELALUI PENDEKATAN SCIENTIFIC TERINTEGRASI PADA MODEL PEMBELAJARAN PROBLEM BASED LEARNING KELAS X MIPA-1 SMAN 4 PEKANBARU - Diant Ratna Andhyka Sari; Zulkarnain Zulkarnain; Syofni Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research that aims to improve of learning process and to improve the ability of reasoning with implementation of an integrated approach to the scientific learning model problem based learning . The subject of this research is student of class X MIPA-1 SMA Negeri 4 Pekanabru in academic years 2018/2019, which total of 36 students, 13 boys and 23 girls. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instruments of data collection were observation sheets and tests of mathematical reasoning abilities. The observation sheet were analyzed by descriptive narrative analysis technique, while the mathematical reasoning ability test were analyzed by descriptive statistical analysis techniques. From qualitative analysis, Students are seen to be actively participating and increasingly independent in the learning process carried out. The results of this study indicate an increase in mathematical reasoning ability can be seen from the number of students who achieved the score in criteria good and very good increased from the base score 4 (11.1%) to the test I amounted to 17 people (47.41%) and test II amounted 29 people (80.5%). Thus it can be concluded the application of integrated scientific approach to the problem based learning learning model can improve the learning process and improve the mathematical reasoning abilities of students in class X MIPA-1 Pekanbaru SMA Negeri 4 in the odd semester of the 2017/2018 school year on the subject matter of rational inequality and irrational and SPLTV.Key Words: Mathematical Reasoning Ability, Scientific, Problem Based Learning Class Action Research